Heavy Metal Accumulation in the Intestinal Tapeworm Proteocephalus macrophallus Infecting the Butterfly Peacock Bass (Cichla ocellaris), from Southeastern Brazil - Leite, Lucas A. R. [UNESP]; Januário, Felipe F.; Padilha, Pedro M. [UNESP]; do Livramento, Emmyle T. C.; de Azevedo, Rodney K.; Abdallah, Vanessa D. (Springer Nature, 2019)
Here we evaluate the potential of heavy metal accumulation of Proteocephalus macrophallus parasitizing the Butterfly Peacock Bass (Cichla ocellaris). A total of 19 fish specimens were collected. From the hosts, samples of intestine, liver, muscle, and parasites were taken. Heavy metal concentrations (Al, As, Ba, Cd, Cr, Fe, Hg, Mg, Mn, Ni, Pb, Ti, and Zn) were obtained using Atomic Absorption Spectrometry. All analyzed elements was found in higher concentrations in the parasites comparing to its host tissues. The bioconcentration factors were higher in the intestine, varying between 5.91 (Ti) to 8.00 (Ba), followed by the muscle, 1.88 (Mg) to 6.39 (Zn), and liver, 1.67 (Al) to 2.02 (Ba). These results show that at the infection site heavy metal concentrations are reduced, since the elements are absorbed directly from the intestinal wall by the parasites. In general, P. macrophallus presents a reasonable capacity of metal accumulation comparing to its hosts.
Keywords: Bioaccumulation patterns; Environmental parasitology; Fish endoparasites; South America; Tucunaré